Peranan Radio Republik Indonesia Yogyakarta Dalam Pelestarian Karawitan - KRISWANTO - (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
The Role of Indonesian Republic Radio of Yogyakarta in Preserving Karawitan. This article discussesthe role of Indonesian Republic Radio (RRI) Yogyakarta in the preservation of karawitan. RRI Yogyakarta –bornthrough MAVRO (1934) and Japan Radio Hosokyoku (1942), offi cially established on September 11, 1945- is aplace for the existence of Uyon uyon Manasuka. Uyon-uyon Manasuka –originally known as Doyo Mardowo– becomesone of the prime shows in RRI Yogyakarta on the struggle of Ki Tjokrowasito who later became the boss. Thecharacteristics of uyon-uyon Manasuka which were different from uyon uyon Hadiluhung Sultan Palace and Uyonuyon Muryoraras Pura Paku Alaman, enrich the cultural treasures of Yogyakarta. Since its birth until now, its existencestill gets its own place for people of Yogyakarta. Even present society is still getting involved directly throughinteractive contacts. Besides uyon-uyon Manasuka, RRI Yogyakarta also facilitates the activities of community-uyonuyon packed in lunch-uyon uyon events